Health Disparities Across Education: The Role of Differential Reporting Error - John Cawley; Anna Choi (Institute for the Study of Labor (IZA), 2015)
One of the most robust findings in health economics is that higher-educated individuals tend to be in better health. This paper tests whether health disparities across education are to some extent due to differences in reporting error across education. We test this hypothesis using data from the pooled National Health and Nutrition Examination Survey (NHANES) Continuous for 1999-2012, which include both self-reports and objective verification for an extensive set of health behaviors and conditions, including smoking, obesity, high blood pressure, high cholesterol and diabetes. We find that better educated individuals report their health more accurately. This is true for a wide range of behaviors and conditions, even socially stigmatized ones like smoking and obesity. Differential reporting error across education leads to underestimates of the true health disparities across education that average 19.3%.
Keywords: I1; I12; I14; I20; I24; I3; 330; health; education; disparities; reporting error